2017
DOI: 10.5696/2156-9614-7.16.58
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Reproductive and Hematological Toxicity Induced in Mice Exposed to Leachates from Petrol, Diesel and Kerosene Dispensing Sites

Abstract: Background.With a population of over 165,000,000, growing at an average rate of 2.7% per annum and an economic growth rate of about 5.7% in the past five years, the market for refined petroleum products in Nigeria is growing. As a result, the number of filling stations is increasing.Objectives.The present study evaluated the reproductive and genetic toxicity of simulated leachate of soil from petrol, diesel and kerosene dispensing sites in a filling station using the murine sperm abnormality test, sperm count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…63 Earlier reports have reported that exposure to leachate induces significant DNA damage in different cell types. [64][65][66] Interestingly, findings of our study also indicated that leachate-induced mitochondrial dysfunction may induce a pro-inflammatory state. In comparison to the controls, the levels of NF-κβ were significantly higher among the cells exposed to the landfill leachate, while significantly higher secreted levels of pro-inflammatory cytokines TNFα, IL-6, and IFN-ƴ were observed in the culture supernatant of landfill leachate exposed cells as compared with their respective controls ( Figure 5).…”
Section: Discussionsupporting
confidence: 61%
“…63 Earlier reports have reported that exposure to leachate induces significant DNA damage in different cell types. [64][65][66] Interestingly, findings of our study also indicated that leachate-induced mitochondrial dysfunction may induce a pro-inflammatory state. In comparison to the controls, the levels of NF-κβ were significantly higher among the cells exposed to the landfill leachate, while significantly higher secreted levels of pro-inflammatory cytokines TNFα, IL-6, and IFN-ƴ were observed in the culture supernatant of landfill leachate exposed cells as compared with their respective controls ( Figure 5).…”
Section: Discussionsupporting
confidence: 61%
“…After the staining with 1% eosin Y for 20 min, a suspension drop was transferred onto a clean slide and air-dried. One thousand sperms per animal were scored from each group for the presence of sperm shape abnormalities [43].…”
Section: Sperm Count and Abnormalitymentioning
confidence: 99%